Adenomatoid odontogenic tumor in two adolescents - Roberto Bonne Comerón; Javier Lozada García; Yolanda Del Toro Gámez (Centro Provincial de Información de Ciencias Médicas, 2020)
Two cases reports of adolescents from both sexes are described, they presented edemas in the left side of the maxillary with dental reabsorption and in the anterior portion of the maxillary, respectively. The histopathology revealed an intraosseous folicular variety of the   adenomatoid odontogenic tumor. The surgical treatment used was an enucleation with satisfactory results.